Advances in insect physiology. - Johnson, Scott N.; Hiltpold, Ivan; Turlings, Ted C. J. (Advances in insect physiology, 2013)
This serial provides in-depth reviews on all aspects of insect physiology of use to invertebrate physiologists and neurobiologists, entomologists, zoologists and insect biochemists. This volume explores the current state of knowledge about the behavior and physiology of root herbivores.